The Existence of Beliefs in the Circle of Official Religions in Indonesia - Septiadi, Muhammad Andi; Ramdani, Zulmi (Religion and Policy Journal, 2024)
Research Problem: The religious teachings of ancestors, commonly referred to as "beliefs" in Indonesia, have existed since ancient times but face a dilemmatic position in the context of officially recognized religions. These local belief systems often encounter discrimination and marginalization, despite their coexistence with recognized religions. The tension between local beliefs and state-recognized religions highlights the ongoing challenges of religious tolerance and inclusivity in Indonesia. Research Purposes: This study aims to examine the existence and recognition of local religions within the framework of Indonesia’s official religious policies. It seeks to explore how local beliefs coexist with state-recognized religions and to understand the impact of legal recognition on reducing discrimination against adherents of these belief systems. Research Methods: The research employs qualitative methods to analyze the historical, sociocultural, and legal dynamics affecting local religions in Indonesia. It draws from case studies, legal documentation, and interviews to provide an in-depth understanding of the issue. Results and Discussion: The findings reveal that adherents of local religions often experience discrimination, stemming from their exclusion from official religious recognition. The Constitutional Court's decision No. 97/PUU-XIV/2016 marked a significant turning point, granting legal acknowledgment to local belief systems and addressing some aspects of discrimination. Despite these advances, tensions remain, but official religions generally promote tolerance and foster coexistence among diverse communities. Research Implications and Contributions: This study highlights the importance of fostering tolerance and inclusivity in multicultural societies. It contributes to understanding the challenges faced by local belief systems in Indonesia and underscores the need for policy and societal efforts to strengthen religious harmony. The findings also provide a foundation for further research on the interplay between legal recognition, religious diversity, and social cohesion.